Frequencies and concentrations of agrochemicals and their impact on the production costs of potato crops - Guevara Gómez, Gabriel Emilio (2021)
The objective of this research is to evaluate the behavior of the incidence level of four phytosanitary problems Phytophthora infestans, Alternaria solani, Phthorimaea operculella and nematodes, in the face of chemical combat carried out by a potato producer (Solanum tuberosum) from the Tierra Blanca sector of Cartago; as well as the influence that the combat of phytosanitary problems has on the productive cost. A descriptive and field investigation was carried out, where the quantity of healthy plants and plants with symptoms of Phytophthora infestans and Alternaria solani was measured weekly throughout the potato production cycle; and the number of captured individuals of Phthorimaea operculella. In addition, in week 0, 10 and 15 of the cycle, a diagnosis of nematodes in the soil was carried out, to evaluate the population behavior during the production cycle. In addition, the types of agrochemicals, their concentration and quantity applied in the crop, the   frequency in which the applications were carried out and the cost associated with these applications were recorded. The main results were that establishing the crop in the dry season favors a decrease in the incidence level of fungal diseases but increases the incidence of Phthorimaea operculella; the rational use of insecticides based on emamectina benzoate, Dimethoate, among others; determine a fast and reliable healing action when the incidence level exceeds the economic damage threshold. The application of inputs based on Etoprofos (0-ethyl-S-S-dipropylphosphorodithioate) in the sowing stage reduced the initial populations of Criconemella sp, Pratylenchus sp and Globodera spp by 78%, 25% and 86% respectively. The combat of phytosanitary problems corresponds to 15% of the total productive cost of potato cultivation.